Decision-making accuracy of soccer referees in relation to markers of internal and external load - McEwan, G. P.; Unnithan, V. B.; Easton, C.; Glover, A. J.; Arthur, R. (European Journal of Sport Science, 2024)
This study examined the relationships between the decision-making performances of soccer referees and markers of physiological load. Following baseline measurements and habituation procedures, 13 national-level male referees completed a novel Soccer Referee Simulation whilst simultaneously adjudicating on a series of video-based decision-making clips. The correctness of each decision was assessed in relation to the mean heart rate (HR), respiratory rate (RR), minute ventilation (VE), perceptions of breathlessness (RPE-B) and local muscular (RPE-M) exertion and running speeds recorded in the 10-s and 60-s preceding decisions. There was a significant association between decision-making accuracy and the mean HR (p = 0.042; VC = 0.272) and RR (p = 0.024, VC = 0.239) in the 10-s preceding decisions, with significantly more errors observed when HR = 90% of HRmax (OR, 5.39) and RR = 80% of RRpeak (OR, 3.34). Decision-making accuracy was also significantly associated with the mean running speeds performed in the 10-s (p = 0.003; VC = 0.320) and 60-s (p = 0.016; VC = 0.253) preceding decisions, with workloads of =250 m·min-1 associated with an increased occurrence of decisional errors (OR, 3.84). Finally, there was a significant association between decision-making accuracy and RPE-B (p = 0.021; VC = 0.287), with a disproportionate number of errors occurring when RPE-B was rated as "very strong" to "maximal" (OR, 7.19). Collectively, the current data offer novel insights into the detrimental effects that high workloads may have upon the decision-making performances of soccer referees. Such information may be useful in designing combined physical and decision-making training programmes that prepare soccer referees for the periods of match play that prove most problematic to their decision-making.